Cost-effectiveness of sacubitril/valsartan for the treatment of patients with heart failure with reduced ejection fraction in Portugal. (3rd March 2020) - Borges, Margarida; Afonso-Silva, Marta; Laires, Pedro A.; Gouveia, Miguel; Alarcão, Joana; Ascenção, Raquel; Costa, João
ABSTRACT: Objectives: This study assesses the cost-effectiveness of sacubitril/valsartan versus enalapril in patients with symptomatic heart failure with reduced ejection fraction (HFrEF). Methods: We used a previously developed Markov model calibrated with patient-level data from the PARADIGM-HF trial, adapted to the Portuguese setting. The model considers two health states (alive or dead) and uses regression analyzes to estimate hospitalizations and deaths over time. A panel of experts estimated resource consumption in the outpatient setting. To estimate resource consumption with hospitalizations, the National Health Service Diagnosis Related Groups database was used. Unit costs were based on national legislation, and on the Infomed database. The model considers a societal perspective, a time horizon of 30-years, and a 5% annual discount rate. Sensitivity analyses assessed the robustness of results. Results: Sacubitril/valsartan increases life expectancy by 0.5 life-years, corresponding to 0.4 incremental quality adjusted life-years (QALY) versus enalapril. The estimated incremental cost-effectiveness ratio (ICER) is 22, 702€/QALY. Sensitivity analysis shows that results are robust, but sensitive to the parameter estimates of the cardiovascular survival curve. Conclusion: Sacubitril/valsartan is a cost-effective therapeutic option in the treatment of Portuguese patients with HFrEF and translate into significant health gains and increased life expectancy versus the current standard of care.